High Performance Liquid Chromatography-Diode Array Detector Method for the Determination of Tartrazine and Indigotine - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2013)
A quantification method was developed for indigotine and tartrazine by high performance liquid chromatography and diode array (DAD) detector. Mobile phase consisted of 6 mM tetrabutylammonium hydrogensulphate solution (TBAHS)/ACN (57:43) with 1 mL min(-1) flow rate, A Phenomenex, Luna, ODS-2 RP-C18(2) (5 mu m, 4.6 mm x 250 mm) column and Agilent 1100 Model DAD detector was used. The wavelength used was 610 nm for indigotine and 427 nm for tartrazine (band width: 4 nm). Efficient separation was obtained by using 0.3 mol L-1 acetate buffer (pH: 4.70) for the dilution of the standard stock solutions to obtain the working solutions. For indigotine, linearity was obtained in the concentration range of 1.096-16.4 mu g mL(-1), y = 561,01x + 5.978 (r(2) = 0.9999); limit of detection (LOD) and limit of quantification (LOQ) were determined as 0.25 and 0.82 mu g mL(-1), respectively. For tartrazine, linearity was obtained in the concentration range of 3.79-38 mu g mL(-1), y = 568.25x -49.029 (r(2) = 0.9997); LOD and LOQ were determined as 1.095 and 3.644 mu g mL(-1), respectively. System suitability parameters theoretical plates (N), tailing factor (T), resolution (R) and retention factor (k') were reported. The possible impurities, counterfeits and degradation products (totally related substances) were assessed for indigotine and tartrazine which were supplied from the pharmaceutical and food companies. The results of the over loadings and the forced degradation studies showed that indigotine from the food company was containing different kinds of related substances. Indigotine and tartrazine from the pharmaceutical company were containing these substances in insignificant amounts, which were used as the standards in this study. Indigotine was stable in 0.5 M HCl solutions, but degradable in a small scale in neutral solutions; tartrazine was stable in neutral solutions, not stable in 0.5 M HCl solutions at 80 degrees C. While the tartrazine peak lost its symmetry and gave a front; the indigotine peak totally disappeared with 0.5 N NaOH and H2O2 3 % solutions at 80 degrees C. The developed method was applied to the samples of a local soft drink and a medicine in the dragee form. The recovery was 81.49 % for indigotine; 84.83 % for tartrazine for the soft drink; 90.15 % for indigotine for the dragee. Tartrazine couldn't be determined in the dragee due to the double peaks. The amounts of indigotine and tartrazine were found in the soft drink and dragee under the regulatory limits. While the founded amounts of indigotine and all related substances differed in the batches of the soft drink, there was no significant difference in the batches of dragees.
Keywords: Indigotine; Tartrazine; Tetrabutylammoniun hydrogen sulphate; Reversed phase liquid chromatography; ELECTROSPRAY MASS-SPECTROMETRY; COMPONENT REGRESSION METHODS; SYNTHETIC FOOD COLORANTS; YELLOW NO-5 TARTRAZINE; SUNSET-YELLOW; LEAST-SQUARES; SPECTROPHOTOMETRIC DETERMINATION; COMBINED BENZIDINE; PONCEAU 4R; DYES